Miss Benson's beetle : a novel - Joyce, Rachel (The Dial Press, 2020)
"It is 1950. London is still reeling from World War II, and Margery Benson--a sensible schoolmarm and lonely spinster--is just trying to get through life. But one day, she reaches her breaking point, abandoning her job and her tidy, circumscribed life, to set out on an expedition to the other side of the world in search of an insect that may or may not exist: the golden beetle of New Caledonia, Margery's childhood obsession ever since her father gave her a book on cryptozoology right before he killed himself. The assistant Margery hires to accompany her, Enid Pretty, in her pink hat and pompom sandals, is not the companion she had in mind. But together they will find themselves drawn into an adventure that exceeds all expectations: a cross-ocean voyage to a remote island covered with dense jungle--the last place two proper British ladies would expect to find themselves. They must risk everything and break all the rules, but at the top of a mountain deep in the South Pacific they will discover their best selves. This is a charming, uplifting story about the power of belief in all its forms; it is an intoxicating adventure that explores what it means to be a woman; and it is a tender exploration of the transformative power of friendship"--